(untitled) (CIPEEX, 2025)
yThis study investigates how pulmonary rehabilitation can positively influence the control of severe asthma, a chronic condition characterized by intense airway inflammation. Severe asthma leads to persistent symptoms and incapacitates patients, often resulting in frequent hospitalizations. Traditional therapy includes medication, but there is growing interest in non-pharmacological strategies such as aerobic physical training (APT), which has been shown to significantly improve physical capacity, reduce symptoms, and the need for corticosteroids, as well as decrease pulmonary inflammation.Recent studies suggest that APT can help modulate airway inflammation, thereby improving patients’ quality of life and reducing levels of pro-inflammatory cytokines, substances involved in the immune response. Another focus of the study is kinins, polypeptides that contribute to vasodilation and smooth muscle contraction, playing a crucial role in asthma. Bradykinin, one of these kinins, is particularly associated with bronchoconstriction and bronchial hyperresponsiveness, typical symptoms of asthma. The proposed study aims to assess how pulmonary rehabilitation, including aerobic and resistance exercises, can improve the control of severe asthma. The study protocol also includes measuring cytokines and kinins in samples of condensed air and induced sputum. The expectation is that pulmonary rehabilitation can reduce the levels of these inflammatory mediators, resulting in better clinical outcomes and offering a new effective approach to the management of severe asthma.key words: Severe Asthma, Pulmonary, Aerobic Physical Training, Inflammatory Mediators